2012
DOI: 10.1371/journal.pone.0040468
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Diversity Patterns in Sandy Beaches along Environmental Gradients

Abstract: Species richness in sandy beaches is strongly affected by concurrent variations in morphodynamics and salinity. However, as in other ecosystems, different groups of species may exhibit contrasting patterns in response to these environmental variables, which would be obscured if only aggregate richness is considered. Deconstructing biodiversity, i.e. considering richness patterns separately for different groups of species according to their taxonomic affiliation, dispersal mode or mobility, could provide a more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Variables were considered as smooth terms using penalized regression splines with degrees of freedom up to 3 (Hastie and Tibshirani ; Barboza et al. ; Gómez and Defeo ). Residuals were checked for all models.…”
Section: Methodsmentioning
confidence: 99%
“…Variables were considered as smooth terms using penalized regression splines with degrees of freedom up to 3 (Hastie and Tibshirani ; Barboza et al. ; Gómez and Defeo ). Residuals were checked for all models.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we do not believe that variation in seafloor composition is the reason for the differences in clam community composition. The differences in clam community diversity could be influenced by biotic (food availability and intraspecific interactions (Schoeman & Richardson, 2002) and abiotic factors (wave energy (Pruss et al, 2011), beach slope, sand moisture, and salinity (Barboza, Gómez, Lercari, & Defeo, 2012). However, food availability is unlikely to be an issue because interspecific competition is low among suspension feeding bivalves (Stanley 2008).…”
Section: Speciesmentioning
confidence: 99%
“…This is a wide (beach width ca 70 m) dissipative beach with fine to very fine (grain size ¼ 0.20 mm) well-sorted sands, a gentle slope (2.7%), a wide surf zone and high macrofauna richness, total abundance and biomass (Defeo et al, 2001;Barboza et al, 2012). The active dunes are covered by a great abundance of the perennial herb Panicum racemosum (Poaceae) and some halophilous annual species such as Blutaparon portulacoides (Amaranthaceae), Cakile maritima (Brassicaceae) and Calycera crassifolia (Calyceraceae).…”
Section: Study Site and Sampling Designmentioning
confidence: 99%
“…On the other hand, insects are the most abundant terrestrial invertebrate group inhabiting coastal dunes and the supralittoral fringe of sandy shores, playing a key role in trophic webs (McLachlan and Brown, 2006). Recent deconstructive analyses based on taxonomy indicated that species richness of these four taxa increased from reflective (steep slopes, coarse sands) to dissipative (flat slopes, fine sands) beaches (Defeo and McLachlan, 2011;Barboza et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation